Kajian Pengembangan Desa Tradisional Menjadi Desa Wisata: Desa Pelang Kenidai, Sumsel - Randy Rizal; Sisca Novia Angrini; Reny Kartika Sary (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, Indonesia, 2023)
Pagar Alam City has one of the old villages that has been included in the most popular indigenous community at the Anugrah Pesona Indonesia (API) award. The village is Pelang Kenidai which still maintains its ancestral values and traditions with the existence of its traditional house known as Ghumah Baghi (Rumah Bari) which is estimated to be up to 200 years old. This issue had become a government program in increasing tourism in Pagar Alam. So that it is necessary to develop a special strategy to help bring out the tourism potential of Pelang Kenidai village. This study aims to formulate the development strategy needed to bring out the tourism potential of Pelang Kenidai Village through the 3A concept (Attractions, Amenities and Accessibility). The research method used is descriptive qualitative with data collection through field observations and literature studies. Data analysis techniques use SWOT analysis to identify the tourism potential that exists in Pelang Kenidai Village. The results of the analysis show that Pelang Kenidai Village can very well be developed into a tourism village through the implementation of a strategy that is formulated with three main aspects of social, cultural and economic as forming the structure of traditional society